Letter from Robert S. Mulliken to Harrison Shull, 1948 - Mulliken, Robert Sanderson (1948)
Letter between Robert S. Mulliken and Harrison Shull, American quantum chemists, concerning living arrangements for Shull in Chicago.
Keywords: Shull, Harrison; Mulliken, Robert Sanderson; Chemists; Illinois--Chicago; Nobel Prize winners; Physicists